INDONESIAN JOURNAL of Islam and Muslim Societies - Marhumah (Postgraduate Program IAIN Salatiga, 2015)
No. Penulis --- Judul Artikel --- Halaman ---1. Ridho Al-Hamdi --- Coping with Religious Tolerance and Gender Equality Comparing Islam and Good Governance Perspectives --- 163-193 --2. Al Makin --- Revisiting Indonesian Public Reaction Against Danish Cartoons Depicting Propehet Muhammad --- 195-229 -- 3. Moch. Fakhruroji --- Mediatization of Religion in ?Texting Culture? : Self-Help Religion and The Shifting of Religious Authority --- 231-254 -- 4. Biyanto --- Pluralism in The Perspective of Semitic Religions --- 255-282 -- 5. Marhumah --- The Roots of Gender Bias : Misogynist Hadiths in Pesantrens --- 283-304